Applied cyber security and the smart grid implementing security controls into the modern power infrastructure - Knapp, Eric D. (Elsevier/Syngress, 2013)
"Understanding how the Smart Grid works first requires an understanding of how industrial networks operate, which in turn requires a basic understanding of the underlying communications protocols that are used, where they are used, and why. There are many systems that comprise the larger system of the "Smart Grid," which utilize both common and open protocols as well as many highly specialized protocols used for industrial automation and control, most of which are designed for efficiency and reliability to support the economic and operational requirements of large distributed control systems. Similarly, industrial protocols are designed for real-time operation requiring deterministic results with continuous availability. Combined together, this blend of open and proprietary networks enables the much larger network of measurements, controls, metering and automation that is the Smart Grid. This amalgam of disparate systems and networks is also a major factor in the cyber security concerns facing the Smart Grid today"--